PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATERI SEGI EMPAT DI KELAS VII SMP SATAP NANUSA DI LALUHE - Monoarfa, Jorry Ferry; Kaunang, Derel Filandy; Samalam, Sindita (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
ABSTRACT. This study aims to determine the improvement of students learning outcomes using problem-based learning models on rectangular material. This research was conducted in class VII SMP Satap Nanusa in Laluhe in the 2018/2019 school year. The type of research used is the pseudo-experiment â€œThe one-shot caseâ€. The research subjects ware class VII with a total of 28 students who ware the treatment class. The instrument used as a test is a matter of essay that has been tested for validity. The hypothesis was tested using the sign test symbolized by Kai Kuadrat (X2) aided SPPS 22.0. at a significant level of Â 0.05 obtained t_count = 57,596 > t_table = 1,706. thus the average posttest score of 75,28 then accepts H1 which means learning rectangular material by using a problem based learning more than KBM 70.Â Â Â Keywords: rectangular, problem-based learning, outcomes.